1999
DOI: 10.1152/ajpgi.1999.276.5.g1213
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the muscularis mucosae in the acid-secreting region of the rabbit stomach

Abstract: It has been suggested that muscularis mucosae excitation may augment gastric acid secretion, implying that this muscle should contract to secretagogues or stimulation of its motor innervation. The aim of this study was to characterize in vitro the responses of the muscularis mucosae in the rabbit gastric corpus to substances that modulate acid release and to intrinsic nerve stimulation. Muscularis mucosae from both fundic and antral ends of the corpus had identical mechanical properties, contracted to ACh, ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Since the neuronally-mediated relaxation of the gastric muscularis mucosae seems to facilitate acid release by opening the gastric glands (Synnerstad et al, 1998), dysfunction of VIPergic nerve-muscularis mucosae transmission may contribute to peptic ulcer (Percy et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the neuronally-mediated relaxation of the gastric muscularis mucosae seems to facilitate acid release by opening the gastric glands (Synnerstad et al, 1998), dysfunction of VIPergic nerve-muscularis mucosae transmission may contribute to peptic ulcer (Percy et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that pathological changes in the transduction pathway between mucosal endocrine cells and primary afferent nerve terminals may lead to decreased motility and secretion in irritable bowel diseases. A number of studies by Percy and his colleagues Percy et al, 1992;Percy et al, 1993a;Percy et al, 1993b;Percy and Warren, 1994;Percy et al, 1997;Percy et al, 1998;Percy et al, 1999;Percy et al, 2001) have revealed that contractility of the muscularis mucosae closely linked with mucosal secretory function and its abnormal motility was concerned in inflammatory bowel diseases. As this physiological transduction mechanism, muscularis mucosae motor activity is translocated into mucosal secretion via the contraction-related PG synthesis and stimulation of non-cholinergic secretomotor neuron (Lawson and Powell, 1987;Percy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations